The impact of order size on stock liquidity: a representative study - Sebastian Stange; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
Liquidity, the ease of trading an asset, strongly varies between different sizes of stock positions. We analyze this aspect using the Xetra Liquidity Measure (XLM), which calculates daily, weighted spread for impatient traders transacting against the limit order book. For this measure, we have data for 160 German stocks over 5.5 years, which allows us a representative analysis of the order-size impact on liquidity cost and its main statistical characteristics. We find that in the sample period average liquidity costs rose to over 100bp in large DAX and to 460bp in large SDAX positions. Over the last 5.5 years, liquidity has equally improved across all order sizes. Liquid position sizes, however, suffered less badly during the recent sub-prime crises, which represents another type of the flight-to-liquidity. As the basis for further theoretical analysis, we find that trends in liquidity levels and inefficiencies in liquidity prices of large positions generate non-normality in the liquidity distribution. We also show that - as a rule of thumb - liquidity of an order size relative to market value and transaction volume is constant across stocks and time. While order size is not the most important liquidity determinant, doubling order size increases liquidity cost by 5-10% on average when accounting for other differences in stocks.
Keywords: G10; G32; 330; asset liquidity; liquidity cost; price impact; weighted spread; Xetra liquidity measure (XLM); Wertpapierhandel; Wertpapieranalyse; Börsenkurs; Deutschland